ANALISIS YURIDIS TERHADAP KRITERIA UNSUR KEBARUAN PADA PATEN SEDERHANA SEBAGAI DASAR GUGATAN PENGHAPUSAN HAK ATAS PATEN SEDERHANA (STUDI PUTUSAN MAHKAMAH AGUNG NO. 167.K/PDT.SUS-HKI/2017) - PARADA APRIZAL (PREMISE LAW JURNAL, 2018)
Simple patent rights are exclusive rights granted by the Office of the Patent Directorate to patent holders to realize new inventions, whether in the form of products or a particular process. Law No. 13 of 2016 concerning Patents has determined that inventions that can be given to simple patents are only inventions that contain elements of novelty or which contain elements of progress. The type of research used in this research is normative legal research. The nature of this research is analytical descriptive. The results of the discussion of the problems that arise in this research invention is a new technology that has never existed before, the invention can be applied as a technology in a product, invention is an improvement of the invention that has been found previously that is applied into a product. Located or if the defendant is outside the territory of Indonesia, the claim is submitted to the Commercial Court in the Central Jakarta District Court. that a simple patent belonging to the defendant contains elements of novelty which is an improvement of the invention that has been the plaintiff's previous patented property in terms of refinement of the plaintiff's invention, so that the invention that has been patented by the defendant does not contain elements of equality or does not imitate the plaintiff's patented invention.Keywords: Simple Patents, Elements of Novelty and Simple Patent Removal